2019
DOI: 10.3390/microorganisms7050127
|View full text |Cite
|
Sign up to set email alerts
|

Biocidal Effectiveness of Selected Disinfectants Solutions Based on Water and Ozonated Water against Listeria monocytogenes Strains

Abstract: The aim of this study was to compare the biocidal effectiveness of disinfectants solutions prepared with ozonated and non-ozonated water against Listeria monocytogenes. Six L. monocytogenes strains were the research material (four isolates from food: meat (LMO-M), dairy products (LMO-N), vegetables (LMO-W), and fish (LMO-R); one clinical strain (LMO-K) and reference strain ATCC 19111). The evaluation of the biocidal effectiveness of disinfectant solutions (QAC—quaternary ammonium compounds; OA—oxidizing agents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 27 publications
0
9
1
Order By: Relevance
“…2011; Skowron et al . 2019); however, this was not the case in this study. Based on the results from the pilot‐scale study, a peroxide‐based biocide would be a potential alternative for the mushroom industry.…”
Section: Discussioncontrasting
confidence: 77%
See 2 more Smart Citations
“…2011; Skowron et al . 2019); however, this was not the case in this study. Based on the results from the pilot‐scale study, a peroxide‐based biocide would be a potential alternative for the mushroom industry.…”
Section: Discussioncontrasting
confidence: 77%
“…This is similar to the findings of other studies (Knowles and Roller 2001; Cruz and Fletcher 2012; Skowron et al . 2018, 2019). BP10 had 1·6‐log less reduction of L. monocytogenes biofilm in dirty conditions but this was not statistically significant ( P > 0·05).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, in this study, as the plasma bubble treatment time increased, the concentration of dissolved O 3 in the water increased, eventually pasteurizing S. Typhimurium by more than 5 log CFU/mL within 5 min. Many studies have been conducted involving the application of O 3 generators for the injection of O 3 gas into water to inactivate microorganisms or decompose organic matter [13,37,38]. Since O 3 can directly oxidize various organic substances and microbial components [12], previous studies have suggested that concentrations of gas-phase or dissolved O 3 in solution are important as oxidative indicators [37,39].…”
Section: Discussionmentioning
confidence: 99%
“…The exposure times on enamel were 8 minutes for hydrogen peroxide and placebo and 19 minutes for oxygen and ozone. Except for the placebo, all were effective in tooth whitening, with differences between the three groups nonstatistically significant [24]. Other researchers have proposed the addition of ozone to hydrogen peroxide for dental bleaching, but is still too early to reach conclusions [25].…”
Section: Resultsmentioning
confidence: 99%